Development of Electroactive Biofiltration Dynamic Membrane for Enhanced Wastewater Treatment and Fouling Mitigation: Unraveling the Growth Equilibrium Mechanisms of Fouling Layer - Chengxin Niu; Wei Shi; Zhouyan Li; Zhiwei Qiu; Yun Guo; Zhiwei Wang (Engineering, 2025)
We developed a strategy involving an electroactive biofiltration dynamic membrane (EBDM) for wastewater treatment and membrane fouling mitigation. This approach utilizes a cathode potential within an anaerobic dynamic membrane bioreactor to establish a growth equilibrium electroactive fouling layer. Over a 240 day operation period, the EBDM exhibited outstanding performance, characterized by an ultralow fouling rate (transmembrane pressure < 2.5 kPa), superior effluent quality (chemical oxygen demand (COD) removal > 93% and turbidity ∼2 nephelometric turbidity units (NTU)), and a 7.2% increase in methane (CH4) productivity. Morphological analysis revealed that the EBDM acted as a biofilter consisting of a structured, interconnected, multilevel dynamic membrane system with orderly clogging. In the EBDM system, the balanced-growth fouling layers presented fewer biofoulants and looser secondary protein structures. Furthermore, the applied electric field modified the physicochemical properties of the biomass, leading to a decrease in fouling potential. Quartz crystal microbalance with dissipation monitoring analysis indicated that growth equilibrium promoted a looser fouling layer with a lower adsorption mass than did the denser, viscoelastic fouling layer observed in the control reactor. Metagenomic sequencing further demonstrated that continuous electrical stimulation encouraged the development of an electroactive fouling layer with enhanced microbial metabolic functionality on the EBDM. This approach selectively modifies metabolic pathways and increases the degradation of foulants. The EBDM strategy successfully established an ordered-clogging, step-filtered, and balanced-growth electroactive fouling layer, achieving a synergistic effect in reducing membrane fouling, enhancing effluent quality, and improving CH4 productivity.